Water operator partnerships: Peer learning and the politics of solidarity in water and sanitation service provision. (17th October 2018) - Beck, Andrea
Abstract : The limitations of public–private partnerships as a way to finance and manage water and sanitation systems in developing countries have become increasingly evident since the 2000s. In response, scholars have begun to inquire about "alternatives to privatization, " with a focus on strengthening social equity and universality in access to essential services. Among the alternatives discussed are so‐called Water Operator Partnerships (WOPs), which have been promoted globally since 2006 with support from the United Nations. Today, more than 200 such peer‐learning partnerships have been formed between water and sanitation operators around the world. Yet, academic research on WOPs is still in its infancy. This article reviews the existing literature on WOPs, addressing their origins and their global evolution, along with key controversies surrounding private‐sector involvement. Relying on self‐reported WOPs data from a global online database, it further illustrates the North–South distribution and the different spatial scales of peer partnerships to date. What emerges from the analysis is that WOPs have become a proliferating, yet insufficiently understood, partnership modality in the water sector. In identifying entry points for future research, the article suggests that the comparative study of WOPs can shed new light on transnational partnerships, South–South cooperation, and the politics of solidarity in water and sanitation service provision. This article is categorized under: Engineering Water > Sustainable Engineering of Water Human Water > Water Governance Human Water > Rights to Water Abstract : More research is needed on Water Operator Partnerships as a mechanism for realizing Sustainable Development Goal 6 and the human rights to water and sanitation.